PERENCANAAN PROGRAM KOMUNIKASI PARIWISATA DALAM PENGEMBANGAN WISATA MUSLIM FRIENDLY DI KAWASAN JAKARTA PUSAT - Siska Wahyuni; Yeni Nuraeni (Jurnal Sosial Humaniora dan Pendidikan, 2023)
This study analyzes and describes how to plan proper tourism communication, as well as knowing the efforts of the tourism office in developing Muslim-friendly tourism in the Central Jakarta Area. Muslim friendly tourism or formerly known as halal tourism is a new phenomenon in the world of tourism, and has begun to be developed in several countries, both Muslim-majority and non-Muslim countries. In the development of Muslim friendly tourism in Jakarta, communication program planning is needed, in order to achieve the specified targets. The Tourism and Creative Economy Office of DKI Jakarta Province as a policy maker in developing Muslim friendly tourism is responsible for informing Muslim friendly tourism to both domestic and foreign tourists. The research method used is descriptive qualitative, using POAC, Tourism Communication and Symbolic Interaction theory. Data collection is carried out through observation, documentation, and interviews. The results of this study show that the development of Muslim friendly tourism that has been carried out by Disparekraf is realized through an agenda that has been prepared based on the involvement of associations, academics, and competent stakeholders in the field of Muslim friendly tourism. Through the process of source planning, message planning, audience planning, media planning, impact planning, to monitoring and evaluation.